2010
DOI: 10.1517/13543781003724690
|View full text |Cite
|
Sign up to set email alerts
|

Novel treatment approaches to cachexia and sarcopenia: highlights from the 5th Cachexia Conference

Abstract: Cachexia is an illness that may occur in terminal stages of many chronic illnesses including cancer, chronic heart failure, chronic renal failure or chronic obstructive pulmonary disease. Effective treatments are urgently needed in order to improve the patients' quality of life and their survival. We report highlights from the 5th Cachexia Conference held in December 2009 in Barcelona, Spain. Novel therapeutic approaches shown here include melanocortin-4 receptor antagonists, myostatin inhibition, beta-blocker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(34 citation statements)
references
References 23 publications
1
33
0
Order By: Relevance
“…Ferritin, as an acute phase protein, plays a role in inflammatory processes in several chronic diseases, like CHF or cancer, as well as after intensive physical performance and catabolic muscle metabolism [34][35][36]. The moderate increase in serum ferritin, as observed in the professional soccer players after their recovery period, do not seem to be part of an acute phase reaction as other inflammatory parameters are not elevated (Table 4).…”
Section: Discussionmentioning
confidence: 98%
“…Ferritin, as an acute phase protein, plays a role in inflammatory processes in several chronic diseases, like CHF or cancer, as well as after intensive physical performance and catabolic muscle metabolism [34][35][36]. The moderate increase in serum ferritin, as observed in the professional soccer players after their recovery period, do not seem to be part of an acute phase reaction as other inflammatory parameters are not elevated (Table 4).…”
Section: Discussionmentioning
confidence: 98%
“…However, this approach of antibody-based myostatin inhibition was much less effective in a phase I/II trial conducted in adult human subjects with muscular dystrophy, although an insignificant trend toward mildly increased skeletal muscle mass was observed and the myostatin inhibiting antibody (MYO-029) was well tolerated (85). Novel reagents have recently emerged, which block activation of the ActRIIB and therefore inhibit the action of both activin-A and myostatin, which might be more effective (37). Indeed, administration of recombinant ActRIIB as a decoy receptor in mice was able to prevent and reverse cancer-associated cachexia in tumor-bearing mice and even markedly improved mouse survival in this model, although tumor growth itself was not inhibited (97).…”
Section: Biology and Function Of Myostatinmentioning
confidence: 99%
“…The anorexic effects of α-MSH are exerted on other tissues through the melanocortin-3 or -4 receptors. Experiments with α-MSH agonists in animals showed decreased food intake [28] and an inverse effect with antagonists in CHF models [29,30]. There are no in vivo data for humans, but cases of dysfunctional mutations in the human melanocortin-4 receptor causing obesity have been described [31,32].…”
Section: The Melanocortin Systemmentioning
confidence: 99%
“…GH and insulin-like growth factor 1 (IGF-1) are considered to be the corresponding mediators. To date, there have been several clinical trials using ghrelin/ghrelin-mimetics (central and peripheral) that demonstrated increased food intake/appetite [30,[40][41][42][43] and associated elevations in GH and IGF levels in healthy volunteers [44] and in patients with chronic diseases. Its orexigenic effects are controlled by its direct action upon the melanocortin system.…”
Section: Ghrelinmentioning
confidence: 99%